Case Report: Use of Liposomal Amphotericin B in Low Doses in Patients With Visceral Leishmaniasis - Ren, Danfeng; Cao, Wenya; Liu, Xiaojing; Han, Qunying; Fan, Wanhu; Li, Guoliang; Xia, Han; Zhang, Xi (Frontiers in Medicine, 2021)
Background: No consensus has been reached regarding the optimal therapy for visceral leishmaniasis (VL), which affects approximately 12 million people worldwide. Case Presentation: This report described four cases of VL encountered in the First Affiliated Hospital of Xi'an Jiaotong University between October 2019 and December 2020. Of the four patients, one patient experienced relapse after antimonial treatment, and the remaining patients had primary VL (including one patient with impaired kidney function and one patient with hemophagocytic syndrome). All patients received a novel treatment protocol, namely the low-dose L-AmB therapy, which was characterized by a low initial dose, cautious dose escalation, and low-dose therapy as maintenance. All patients were cured without severe complications, and there was no further recurrence during follow-up. Conclusions: This case series demonstrated the safety and efficacy of the low-dose L-AmB therapy for VL patients, providing novel treatment protocol for the VL.